Rękopisy doby staropolskiej prowincji małopolskiej reformatów w Bibliotece Głównej Prowincji Franciszkanów-Reformatów w Krakowie - Szteinke, Anzelm Janusz (Piśmiennictwo zakonne w dobie staropolskiej, 2013)
The old Polish Reformati Friars’ manuscripts of the Lesser Poland province stored in the Main Libraryof the Franciscan-Reformati friars concern the ascetic and intellectual formation, as well as differentaspects of activities developed by monks equal in Poland and elsewhere, where they come live and work.Information which we publish here resists on their preliminary distinction, in which it tries to establishtheir topic and authors.